(untitled) (Bangladesh Journal of Agriculture, 2025)
An experiment was conducted at the Advanced Plant Breeding and Tissue Culture Laboratory of Bangabandhu Sheikh Mujibur Rahman Agricultural University to evaluate the effects of NaCl on rice callus induction and plant regeneration, along with genetic variability assessment through molecular markers. Dehusked seeds of five distinct rice genotypes (Dakshahi, Gondhakasturi, Guamasuri, Duksail, and Khazar) were put on MS medium supplemented with five levels (0, 0.2, 0.4, 0.6 and 0.8%) of NaCl. Developed calli were placed in MS medium for regeneration around 3-6 weeks later. Callus induction and plant regeneration declined with the increase of salinity levels. Dakshahi outperformed the other cultivars in both parameters at different salt concentrations, and it was the only cultivar with callus and regenerated plants at 0.08% NaCl concentrations. To amplify the genomic DNA of parents and somaclones of different varieties, five random amplified polymorphic DNA (RAPD) primers were used. Polymorphic bands were visible in OPD-07 primer. Dakshahi and Khazar were found to have the maximum genetic diversity (0.941). The genetic similarity coefficients between lines demonstrate that the degree of genetic diversity within rice genotypes was quite distinct. The cluster analysis grouped five genotypes into two clusters. The presence of genetic variation in the somaclones of Guamasuri implies the potential of RAPD markers in assessing genetic diversity and validating somaclonal variation. Also, Dakshahi demonstrating the highest tolerance for NaCl stress in both callus induction and plant regeneration, making it a promising candidate for salt-tolerant rice breeding in future. Bangladesh J. Agri. 2024, 49(2): 16-30